How Psychopragmatic Studies Can Be an Approach to Seeing a Pattern of Covid-19 Spread - Wahyudi Rahmat; Alex Darmawan; Maryelliwati Maryelliwati; Hari Adi Rahmad; Aminah Aminah (Ranah: Jurnal Kajian Bahasa, 2023)
The Covid-19 pandemic has caused widespread concern and apprehension among individuals globally, including those residing in Indonesia. This infectious disease primarily affects the respiratory system. This investigation uses psychopragmatic analysis to analyze various types of discourse that may contribute to the propagation of Covid-19 or coronavirus. Specifically, the study will focus on panic and anxiety speech, which are influenced by the speaker's psychological state. The theoretical framework employed in this research is based on Capano (2013). The utilized research methodology is founded on Sudaryanto's (2015) perspective, employing a distribution approach. The findings of this research indicate that a speaker's psychology can impact the development of Covid-19 in other speakers, as evidenced by the influence of panic and anxiety speech. This phenomenon arises from the experience of panic and anxiety, resulting in an excessive manifestation of fear and anxiety. AbstrakPandemi Covid-19 telah menimbulkan kekhawatiran dan ketakutan yang meluas di kalangan individu secara global, termasuk mereka yang berada di Indonesia. Penyakit menular ini terutama memengaruhi sistem pernapasan. Investigasi ini bertujuan untuk menganalisis berbagai jenis wacana yang dapat berkontribusi pada penyebaran Covid-19 atau virus corona dengan menggunakan analisis psikopragmatik. Secara khusus, penelitian ini akan berfokus pada pidato panik dan kecemasan yang dipengaruhi oleh keadaan psikologis pembicara. Kerangka teori yang digunakan dalam penelitian ini didasarkan pada Capano (2013). Metodologi penelitian yang digunakan didasarkan pada perspektif Sudaryanto (2015), dengan menggunakan pendekatan distribusi. Temuan penelitian ini menunjukkan bahwa psikologi seorang pembicara dapat berdampak pada perkembangan Covid-19 pada pembicara lain, terbukti dengan pengaruh pidato panik dan kecemasan. Fenomena ini muncul dari pengalaman panik dan kecemasan, yang mengakibatkan manifestasi ketakutan dan kecemasan yang berlebihan.